Students Perception on Online and Offline Learning : a Comparative Study in English Proficiency Class in English Departmen Universitas Negeri Padang - Nurul Hanisah Nasution; Senorica Yulia Sari (Universitas Negeri Padang, 2023)
Nowadays, education system is conducted through online to the offline learning since COVID-19 decreased. Both are neccesary for learning process in EFL students. This reasearch was conducted in English Proficiency Class in English Department at Padang State University. The responden in this research were two hundred students. This reaserch used quantitave descriptive. This research aimed to see students' perceptions on comparing online and offline learning. Based on the results of the students' learning outcomes showed that the mean score of the students who learned over offline learning in English Proficiency class was 72.96 and who learned in online learning was 62.29. This score indicated that students learning outcomes in offline learning is more effecient compared to the online learning in English Proficiency Class at Padang State University.